Tunable internal quantum well alignment in rationally designed oligomer-based perovskite films deposited by resonant infrared matrix-assisted pulsed laser evaporation. Issue 8 (23rd May 2019) - Dunlap-Shohl, Wiley A.; Barraza, E. Tomas; Barrette, Andrew; Dovletgeldi, Seyitliyev; Findik, Gamze; Dirkes, David J.; Liu, Chi; Jana, Manoj K.; Blum, Volker; You, Wei; Gundogdu, Kenan; Stiff-Roberts, Adrienne D.; et al.
Abstract : RIR-MAPLE enables thin-film deposition of organic–inorganic materials with tunable synergistic photophysics. Abstract : Hybrid perovskites incorporating conjugated organic cations enable unusual charge carrier interactions among organic and inorganic structural components, but are difficult to prepare as films due to disparate component chemical/physical characteristics ( e.g., solubility, thermal stability). Here we demonstrate that resonant infrared matrix-assisted pulsed laser evaporation (RIR-MAPLE) mitigates these challenges, enabling facile deposition of lead-halide-based perovskite films incorporating variable-length oligothiophene cations. Density functional theory (DFT) predicts suitable organic and inorganic moieties that form quantum-well-like structures with targeted luminescence or exciton separation/quenching. RIR-MAPLE-deposited films enable confirmation of these predictions by optical measurements, which further display excited state behavior transcending traditional quantum-well models— i.e., with appropriate selection of specially synthesized organic/inorganic moieties, intercomponent carrier transfer efficiently converts excitons from singlet to triplet states in organics for which intersystem crossing cannot ordinarily compete with recombination. These observations demonstrate the uniquely versatile excited-state behavior in hybrid perovskite quantum wells, and the value of integrating DFT, organic synthesis, RIR-MAPLE and spectroscopy for screening/preparing rationally devised complex structures.